Detecting pigments from gypsum endoliths using Raman spectroscopy: From field prospection to laboratory studies. (6th June 2021) - Němečková, Kateřina; Culka, Adam; Jehlička, Jan
Abstract: Microbial colonisations of gypsum from different sites from Southern Sicily and Eastern Poland were investigated using laboratory‐based Raman microspectrometers and portable Raman spectrometric devices. Selected zones of microbial colonisations of few types of gypsum are described from the point of view of the presence of algae and cyanobacteria. Macrocrystalline gypsum layers in Sicily and Eastern Poland originate from Tertiary sedimentary series. In Southern Sicily gypsum outcrops from late Miocene age were investigated near Scala dei Turchi, Torre Salsa and Siculiana Marina. Polish Tertiary Middle Miocene age examples of gypsum colonisations of decimetre to metre long outcropping gypsum crystals were studied near Chotel Czerwony, Skorocice and Chwalowice. Common microbial pigments were detected: carotenoids were documented in majority of the samples (common Raman bands at around 1525, 1157 and 1004 cm −1 ), Raman spectra of other pigments were recorded in several zones using near infrared excitation (785 nm): chlorophyll (1326, 1285, 1188 and 745 cm −1 ), scytonemin (1593, 1552, 1438 and 1173 cm −1 ) and phycobiliproteins (1275 cm −1 ). Raman microspectrometric investigations of colonisations allow to gather detailed information about pigment distribution in micrometric zones of gypsum samples. Portable instrumentation permits also detection of carotenoids. Observed shifts of positions of Raman features of carotenoids between gypsum samples (and sites worldwide) and relative to reference values are discussed and critically evaluated. Abstract : Using the combination of 532‐nm and 780‐nm lasers allows analysis of endolithic pigment and their distribution in natural environments such as gypsum. Stretching vibrations of carotenoids are found all colonized zones while UV‐protective pigments—scytonemin and gloeocapsin are located only in the zones closer to the surface.